2021
DOI: 10.3389/fspor.2021.683327
|View full text |Cite|
|
Sign up to set email alerts
|

High-Protein Energy-Restriction: Effects on Body Composition, Contractile Properties, Mood, and Sleep in Active Young College Students

Abstract: Background: It is often advised to ensure a high-protein intake during energy-restricted diets. However, it is unclear whether a high-protein intake is able to maintain muscle mass and contractility in the absence of resistance training.Materials and Methods: After 1 week of body mass maintenance (45 kcal/kg), 28 male college students not performing resistance training were randomized to either the energy-restricted (ER, 30 kcal/kg, n = 14) or the eucaloric control group (CG, 45 kcal/kg, n = 14) for 6 weeks. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 137 publications
1
27
0
Order By: Relevance
“…During CR, activation of mTORC1 and its downstream targets, as well as MPS is reduced, while proteolysis appears to be increased (Margolis et al 2016 ; Carbone et al 2014 ; Berryman et al 2017 ); however, the results in this regard are somewhat conflicting (Carbone et al 2019 ). Without any counteracting stimuli (e.g., RT), attenuation of MPS ultimately leads to a negative net protein balance and, hence, to lean tissue loss (Roth et al 2021 ; Pasiakos et al 2013 ). This is supported by the data of athletes taking performance-enhancing drugs who, due to ergogenic effects on protein turnover, do not show significant lean tissue loss (Pasiakos et al 2019 ; de Souza et al 2018 ; Howard et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…During CR, activation of mTORC1 and its downstream targets, as well as MPS is reduced, while proteolysis appears to be increased (Margolis et al 2016 ; Carbone et al 2014 ; Berryman et al 2017 ); however, the results in this regard are somewhat conflicting (Carbone et al 2019 ). Without any counteracting stimuli (e.g., RT), attenuation of MPS ultimately leads to a negative net protein balance and, hence, to lean tissue loss (Roth et al 2021 ; Pasiakos et al 2013 ). This is supported by the data of athletes taking performance-enhancing drugs who, due to ergogenic effects on protein turnover, do not show significant lean tissue loss (Pasiakos et al 2019 ; de Souza et al 2018 ; Howard et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…7 We lowered the effect size to account for individual variability in lean mass loss. 15 An a priori power analysis was performed using G*Power 3.1 (University Duesseldorf, GER) which revealed that 38 participants were required to achieve a power = 0.80, an effect size of f = 0.23, and an α = 0.05.…”
Section: Participant Recruitmentmentioning
confidence: 99%
“…For the daily weigh-ins, the participants reported body mass to the nearest 0.1 kg on their own digital scale wearing only underwear after an overnight fast and after emptying their bladder. The dietary prescription employed during the study was adapted from Roth et al 15 Briefly, during the familiarization phase all participants consumed 45 kcal/kg for weight maintenance, followed by a six-week hypocaloric period (30 kcal/kg); the energy deficit in the hypocaloric intervention is consistent with recommendations for natural bodybuilders during contest preparation. 18 Protein intake was set at 2.8 g/kg fat-free mass (FFM) in both groups throughout the study period, 19 with the remaining energy distributed between carbohydrates and fats based on individual preference.…”
Section: Diet and Exercisementioning
confidence: 99%
See 2 more Smart Citations